Gender identity construction in virtual political communication: Discourse strategies and self-representation practices in social networks - O B Maximova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
The article considers the specifics of gender construction in political virtual communication. The author employs the discursive approach combined with the content analysis to study gender communicative strategies and self-representation practices in social networks. Facebook postings within a viral flash-mob “The Island of the‘90’s” provided the data for the study, and the article explains the rationale for their attribution to political communication. The analysis based on the cognitive model of discourse revealed the three-level structure of flash-mob discourse that reflects different levels of publications involvement into the political context. The comparative analysis of male and female participation in the development of flash-mob discourse helped to identify a pronounced gender asymmetry in both flash-mob discourse structure and its structural levels. The content analysis showed no signs of gender differences disappearance, traditional gender-role patterns weakening or androgyne model manifestation. The results lead to the conclusion that women seem to be more flexible in their representation strategies, and women’s participation in the discourse has less degree of political involvement at all structural levels. The author highlights the theoretical importance of the Internet flash-mob investigation methodology development for the study of virtual political communication.